Causal relationship between bipolar disorder and inflammatory bowel disease: A bidirectional two-sample mendelian randomization study - Wang, Zhe; Wang, Xinyu; Zhao, Xushi; Hu, Zhaoliang; Sun, Dongwei; Wu, Donglei; Xing, Yanan (Frontiers in Genetics, 2022)
Background: Growing evidence suggests a bidirectional association between bipolar disorder (BD) and inflammatory bowel disease (IBD); however, observational studies are prone to confounding, making causal inference and directional determination of these associations difficult. Methods: We performed bidirectional two-sample Mendelian randomization (MR) and selected single nucleotide polymorphisms (SNPs) associated with BD and IBD as instrumental variables (IV). SNPs and genetic associations with BD and IBD were obtained from the latest genome-wide association studies (GWAS) in Europeans (BD: cases/controls: 20352/31358; IBD: 12882/21770; Crohn's disease (CD): 5956/14927; ulcerative colitis (UC): 6968/20464;). The inverse-variance-weighted method was the major method used in MR analyses. MR-Egger, weight mode, simple mode, and weighted median were used for quality control. Results: Genetically predicted BD (per log-odds ratio increase) was significantly positively associated with risk of IBD (OR: 1.18, 95% CI: 1.04–1.33), and UC (OR=1.19, 95% CI: 1.05–1.35), but not CD (OR=1.18, 95% CI: 0.95–1.48). The validation analysis found that combined OR of IBD, CD, and UC increased per log-OR of BD were 1.16(95% CI: 1.02–1.31), 1.20(95% CI: 0.98–1.48) 1.17(95% CI: 1.02–1.35), respectively. In contrast, no causal relationship was identified between genetically influenced IBD and BD. Conclusions: Our results confirm a causal relationship between BD and IBD, which may influence clinical decisions on the management of BD patients with intestinal symptoms. Although the reverse MR results did not support a causal effect of IBD on BD, the effect of the IBD active period on BD remains to be further investigated.